Flow en deportistas mexicanos de alto rendimiento: su relación con aspectos intrínsecos y aptitudinales - Reyes Sosa, Hiram (2023)
The aim of this article was identifying the processes that predict the optimal state of Flow in high performance university athletes. A sample of 75 athletes that participated in the Sinaloa State Universiada and Monterrey´s National Universiada with ages between 18 and 25 years (M = 21,26 SD = 1,89) participated in this research. The results showed that athletes presented higher levels of positive emotions accompanied with optimal state of Flow and lower levels of somatic and cognitive anxiety. Finally, the variables intrinsic motivation, positive affect, hours of training and economic support were the predict optimal state of Flow.